Long Term Survival Analysis of Hepatectomy for Neuroendocrine Tumour Liver Metastases. (12th January 2014) - Cheung, Tan To; Chok, Kenneth S. H.; Chan, Albert C.Y.; Tsang, Simon; Dai, Jeff W. C.; Lang, Brian H. H.; Yau, Thomas; Chan, See Ching; Poon, Ronnie T. P.; Fan, Sheung Tat; Lo, Chung Mau
Abstract : Background. Liver is the commonest site for metastasis in patients with neuroendocrine tumour (NET). A vast majority of treatment strategies including liver directed nonsurgical therapy, liver directed surgical therapy, and nonliver directed therapy have been proposed. In this study we aim to investigate the outcome of liver resection in neuroendocrine tumour liver metastases (NELM). Method. 293 patients had hepatectomy for liver metastasis in our hospital between June 1996 and December 2010. Twelve patients were diagnosed to have NET in their final pathology and their data were reviewed. Results. The median ages of the patients were 48.5 years (range 20–71 years). Eight of the patients received major hepatectomy. Four patients received minor hepatectomy. The median operation time was 418 minutes (range 195–660 minutes). The median tumor size was 8.75 cm (range 0.9–21 cm). There was no hospital mortality. The overall one-year and three-year survivals were 91.7% and 55.6%. The one-year and three-year disease-free survivals were 33.3% and 16.7%. Conclusion. Hepatectomy is an effective and safe treatment for NELM. Reasonable outcome on long term overall survival and disease-free survival can be achieved in this group of patients with a low morbidity rate.